On the Illegitimacy of the „Legal Marxism” (Sergei Bulgakov and Nicolai Berdyaev) - Krasicki, Jan (Hybris, 2018)
The article deals with the question of how Sergei Bulgakov and Nicolai Berdyaev, two spokesmen of the so-called “legitimate Marxism,” approached Marx’s philosophy. The author tries to find out the reasons of their access to and then dismissal of the doctrine. While he stresses the complex character of the former, he also demonstrates that the latter was not a simple act of rejection but was connected with attempts to understand Marx’s socio-economic doctrine on the religious and metaphysical basis.